Feasibility of Single-Port Access (SPA) Laparoscopy for Large Ovarian Tumor Suspected to Be Borderline Ovarian Tumor - Kang, Jun-Hyeok; Noh, Joseph J.; Jeong, Soo Young; Shim, Jung In; Lee, Yoo-Young; Choi, Chel Hun; Lee, Jeong-Won; Kim, Byoung-Gie; Bae, Duk-Soo; Kim, Hyun-Soo; Kim, Tae-Joong (Frontiers in Oncology, 2020)
Objectives: To compare the surgical, pathological and oncological outcomes of single-port access (SPA) laparoscopy against laparotomy for large ovarian tumor (> 15 cm) suspected to be a borderline ovarian tumor (BOT) on preoperative imaging. Methods: A retrospective review of the patients who underwent SPA laparoscopy (SPA Group) or laparotomy (Laparotomy Group) for suspected BOT was performed. Surgical outcomes, including the rates of iatrogenic spillage of tumor contents, and oncological outcomes, such as recurrence-free survival (RFS) and overall survival (OS), were compared between the two groups. Correlation between intraoperative frozen section analysis and permanent pathology results was also assessed. Results: A total of 178 patients underwent surgical treatment for suspected large BOT. Among them, 105 patients with a mean tumor diameter of 20.9 ± 6.5 cm underwent SPA laparoscopy, and the other 73 patients, with a mean tumor diameter 20.2 ± 5.9 cm, underwent laparotomy. The mean operation time did not differ between the two groups (99.1 ± 41.9 min for SPA Group vs. 107.3 ± 35.7 min for Laparotomy group, p = 0.085). There was no difference in the occurrence of iatrogenic spillage of tumor contents between the groups either (11.4% in the SPA Group vs. 6.8% in the Laparotomy Group, p = 0.381). However, the postoperative complication rates were significantly higher in the Laparotomy Group compared with SPA Group (16.4% vs. 5.7%, p = 0.025). The surgical approach was not associated with the misdiagnosis rates of frozen section analysis (19% in the SPA Group vs. 26% in the Laparotomy Group, p = 0.484). The most common histologic type of the tumors was mucinous in both groups. Conclusion: SPA laparoscopy is feasible, safe, and not inferior to laparotomy for surgical treatment of large ovarian tumors that suspected to be BOT on preoperative imaging.